ANALYSIS OF FACTORS THAT INFLUENCE TRADERS' INCOME IN OLD MARKETS COMPARED TO MODERN MARKETS - Deni Iskandar (Adisam Publisher, 2024)
Traditional markets are still a very important center of economic activity for some people in Indonesia. Directly, traditional markets have natural competitive advantages that their competitors do not have. The advantages of traditional markets include strategic locations, wide sales areas, a complete variety of goods, low prices, and a bargaining system that shows closeness between sellers and buyers. The development of the modern market has an impact on small traders' businesses, if seen from business law, that is, if small traders are unable to compete and provide the best service to consumers when viewed in terms of price, product quality, comfort, then consumers will be abandoned. The presence of a modern market adjacent to a traditional market could cause the existence and presence of basic food traders in traditional markets to decline so that the result will have an impact on the continuity of basic food traders in the market, one of which is that basic food traders experience losses in terms of income which makes their business go out of business. The existence of an art market Modern technology can be a dilemma for traders who have small scale capital and can potentially cause a decrease in traders' income in traditional markets.